Multi-omics study reveals differential expression and phosphorylation of autophagy-related proteins in autism spectrum disorder - Eden Deri; Shashank Kumar Ojha; Maryam Kartawy; Igor Khaliulin; Haitham Amal (Scientific Reports)
Abstract Our multi-omics study investigated the molecular mechanisms underlying autism spectrum disorder (ASD) using Shank3 Δ4–22 and Cntnap2 −/− mouse models. Through global- and phospho- proteomics of the mouse cortex, we focused on shared molecular changes and found that autophagy was particularly affected in both models. Global proteomics identified a small number of differentially expressed proteins that significantly impact postsynaptic components and synaptic function, including key pathways such as mTOR signaling. Phosphoproteomics revealed unique phosphorylation sites in autophagy-related proteins such as ULK2, RB1CC1, ATG16L1, and ATG9, suggesting that altered phosphorylation patterns contribute to impaired autophagic flux in ASD. SH-SY5Y cells with SHANK3 gene deletion showed elevated LC3-II and p62 levels, indicating autophagosome accumulation and autophagy initiation, while the reduced level of the lysosomal activity marker LAMP1 suggested impaired autophagosome-lysosome fusion. The study highlights the involvement of reactive nitrogen species and nitric oxide (NO) on autophagy disruption. Importantly, inhibition of neuronal NO synthase (nNOS) by 7-NI normalized autophagy markers levels in the SH-SY5Y cells and primary cultured neurons. We have previously shown that nNOS inhibition improved synaptic and behavioral phenotypes in Shank3 Δ4–22 and Cntnap2 −/− mouse models. Our multi-omics study reveals differential expression and phosphorylation of autophagy-related proteins in ASD but further investigation is needed to prove the full involvement of autophagy in ASD. Our study underscores the need for further examination into the functional consequences of the identified phosphorylation sites, which may offer potential novel therapeutic autophagy-related targets for ASD treatment.